Uso de ácido acético (vinagre de maçã) na dieta de vacas em lactação: produção, composição e qualidade do leite - César Victor Brandão Gontijo (2012)
To evaluate the use of acetic acid (apple cider vinegar, 4% acidity) in the diet of lactating cows, an experiment was conducted where different volumes of vinegar (0, 30, 60, 90 e 120 ml/animal dia-1) were added to the diet. Five Girolando cows, 80 d in milk, producing 18 kg daily and weight 517,6 kg. The experimental diet was based on corn silage as forage and concentrate was based on ground corn and soybean meal. The vinegar was offered twice a day, individually, added to 0.5 kg of the concentrate. The forage and the other part of the concentrate were offered as a total mix ration ad libitum twice a day. The experimental design was a 5x5 Latin Square design and the responses were evaluated using a linear regression model to the 5 % significance. The supplementation with apple vinegar caused positive linear effects increasing the milk production (p<0.05), and the total daily productions of milk fat (p<0.05), milk protein (p<0.05) and total solids (p<0.05). There was a negative linear effect on the total bacterial count (TBC) of the milk, where the addition of 120 ml of vinegar resulted in the lowest TBC count. It was observed a negative linear effect on pH and ammonia nitrogen (N-NH3) been the lowest values observed when 120 ml of vinegar was added. There was a significant adjustment of the linear regression for the volatile fatty acids acetate and propionate. The results showed that 120ml vinegar supplementation/cow day-1 increased the milk production and as consequence there were increases in the total yield of milk fat, milk protein and milk solids and that was also observed a reduction in the TBC.